2015
DOI: 10.1016/j.anclin.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Physiology Considerations in Geriatric Patients

Abstract: Synopsis A person’s physiology is ever-changing at the structural, functional, and molecular levels as they age, and every major organ system experiences physiologic change with time. The changes to the nervous system result mostly in cognitive impairments, the cardiovascular system result in higher blood pressures with lower cardiac output, the respiratory system result in a reduction of arterial oxyhemoglobin, the gastrointestinal system result in delayed gastric emptying with a reduction of hepatic metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
85
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(109 citation statements)
references
References 28 publications
(124 reference statements)
2
85
1
6
Order By: Relevance
“…6 The physiology of the elderly changes on structural, functional and molecular levels, in addition to the physiological alterations that the organs suffer over the years. 7 Different age groups have different taste perceptions; for example, the level of flavor perceived by children differs from adults, and may also differ between groups of people. 8 To have the same perception of taste, individuals aged over 80 require a more intense taste stimulus than people aged 20.…”
Section: Introductionmentioning
confidence: 99%
“…6 The physiology of the elderly changes on structural, functional and molecular levels, in addition to the physiological alterations that the organs suffer over the years. 7 Different age groups have different taste perceptions; for example, the level of flavor perceived by children differs from adults, and may also differ between groups of people. 8 To have the same perception of taste, individuals aged over 80 require a more intense taste stimulus than people aged 20.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolizma yavaşladığından anestezik ilaçların etkileri uzar. Postoperatif deliryum daha sık oluşur (3) . Tüm bunların sonucu olarak da anesteziye bağlı komplikasyonlar artar.…”
Section: Introductionunclassified
“…Physiological changes of ageing include changes in the central nervous system, cardiorespiratory system, renal system, endocrine system, gastrointestinal and musculoskeletal system. 4 Previous study by Shehab Mahmoud El-Kader suggested that a decrease in the ability to generate force in the lower extremity muscles contribute to balance impairment and falling. 2 According to the study by Vadhaiya Ashwin, there is a correlation between the ankle range of movement (ROM) and balance in elderly population.…”
Section: Introductionmentioning
confidence: 99%